Integrating strategic foresight processes to improve regional planning : Four intuitive scenarios for Wales’ regional futures - Jenkins, Tarian (My University, 2021)
With national foresight activities gaining widespread use as a means of analysing the long-term perspectives, the potential of sub-national or regional actors are equally a vital com-ponent within European modes of governance. It therefore becomes important to support regional foresight processes as regional actors take steps towards harnessing the potentials of activities for developing common visions of futures, for a more robust approach to decision making. Following the successes of the 2015 Futures Well-being Act, increased interest from the Welsh Government to improve planning and foresight activities acts as the case illustration for integrating foresight processes to improve regional planning. Therefore, this thesis acts as a practical guide for regional actors wishing to implement foresight processes drawing from Hiltunen’s (2013) ‘Building a future proof strategy mo-del’. How to integrate strategic foresight processes to improve regional planning is exami-ned through two questions. Firstly, how to produce high quality scenarios? Secondly, how to secure the use of regional scenarios? The scenario framework draws upon Dator’s (2009) four future archetypes and the theory of path creation, whilst the construction process is built around a threefold quality criteria proposed by Glenn (2003) and the Intuitive logic approach. The scenario construction process utilises a number of methods for the gathering, organizing and sense making of data. As principle examples of what high quality scenarios consist of, the qua-lity criteria in combination with the Intuitive logic approach are applied to guide the re-search and construction processes. Ensuring the use of the scenarios employs the use of three elements ‘transparency, credibility and legitimacy. The implementation of each element plays a vital role throughout the research process as a systematic evaluation fra-me to ensure the use of scenarios. The goal of the study was to produce high quality scenarios and ensure their use by regional planners. The results of implementing the criteria for scenario construction demonstrate the need for further research to be conducted on scenario quality criteria. The three elements whilst being a derivative of evaluation frameworks proposed by Pii-rainen et al. (2012) and van der Steen & van der Duin (2012), contribute to the evaluati-on of exisiting and ongoing studies. Therefore, increasing the credibility of such future activities.
Keywords: strategic foresight, regional foresight, scenario planning, trend analysis, regional planning, path creation, regional futures